5.62b Hydraulic Circuit-8: Cylinder speed control using series pressure compensated flow control and check valves - M.Galal Rabie (McGraw-Hill's AccessEngineering., 2024)
This circuit illustrates the control of cylinder extension speed using a series pressure compensated flow control valve. In the reverse direction, the parallelly connected check valves ensures free fluid flow and a maximum piston speed.